2016
DOI: 10.1016/j.dib.2015.12.055
|View full text |Cite
|
Sign up to set email alerts
|

NSAIDs attenuate hyperalgesia induced by TRP channel activation

Abstract: Transient receptor potential (TRP) cation channels have been extensively investigated as targets for analgesic drug discovery. Because some non-steroidal anti-inflammatory drugs (NSAIDs) are structural analogs of prostaglandins (mediators of inflammation) and NSAIDs attenuate heat nociception and mechanical allodynia in models of inflammatory and neuropathic pain, we examined three widely used NSAIDs (diclofenac, ketorolac, and xefocam) on the activation of TRPA1 and TRPV1 channels using thermal paw withdrawal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 10 publications
0
12
0
2
Order By: Relevance
“…Other drugs acting via TRPV1 include NSAIDs such as diclofenac, ketorolac, and xefocam. These molecules applied topically in rats inhibited pain behavior, most probably by inhibition of TRPV1 and TRPA1 channels [ 169 ]. Endocannabinoids and phyto-cannabinoids may exert their antinociceptive effect via TRPV1 activation, as was shown in preclinical studies.…”
Section: Molecular/cellular Mechanisms Of Topical Treatments In Patients With Localized Neuropathic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Other drugs acting via TRPV1 include NSAIDs such as diclofenac, ketorolac, and xefocam. These molecules applied topically in rats inhibited pain behavior, most probably by inhibition of TRPV1 and TRPA1 channels [ 169 ]. Endocannabinoids and phyto-cannabinoids may exert their antinociceptive effect via TRPV1 activation, as was shown in preclinical studies.…”
Section: Molecular/cellular Mechanisms Of Topical Treatments In Patients With Localized Neuropathic Painmentioning
confidence: 99%
“…Topically administered NSAIDs may interfere with the nociceptive pathway by their ability to decrease the synthesis of proinflammatory PGs through inhibition of cyclooxygenase COX-2. Preclinical studies showed that locally administered diclofenac may also act on several ion channels (Nav, TRPV1, TRPA1, TRPM3, K + , NMDAR) at peripheral neurons, resulting in antinociception [ 138 , 169 , 226 , 228 , 229 ]. Peripheral antinociception induced by diclofenac may rely on release of noradrenaline and interaction with α1, α2C, and β-adrenoreceptors [ 230 ].…”
Section: Molecular/cellular Mechanisms Of Topical Treatments In Patients With Localized Neuropathic Painmentioning
confidence: 99%
“…Many other compounds, drugs, and chemicals are thought to interact with TRP channels. Based on TRPA1-induced hyperalgesia, Nozadze et al investigated nonsteroidal anti-inflammatory drugs with regard to their potential to counteract TRPA1-induced side-effects [ 68 ]. In the in vivo study, diclofenac, ketorolac, and xefocam have proven to diminish AITC-induced TRPA1 activation, and hyperalgesia was mitigated [ 68 ].…”
Section: Organ-specific Expression Of Chemosensing and Sensory Trpmentioning
confidence: 99%
“…Notably, capsaicin, the main active ingredient of hot chili peppers, is a potent, highly selective TRPV1 agonist, and a capsaicin 8% patch relieves pain in patients with peripheral neuropathic pain [29] (Table 1). Interestingly, NSAIDs also appear able to desensitize TRPV1 channels—a mechanism supposed to participate in the NSAID-mediated attenuation of hyperalgesia [30].…”
Section: Introductionmentioning
confidence: 99%